2022
DOI: 10.1038/s41536-021-00199-z
|View full text |Cite
|
Sign up to set email alerts
|

OCT4-induced oligodendrocyte progenitor cells promote remyelination and ameliorate disease

Abstract: The generation of human oligodendrocyte progenitor cells (OPCs) may be therapeutically valuable for human demyelinating diseases such as multiple sclerosis. Here, we report the direct reprogramming of human somatic cells into expandable induced OPCs (iOPCs) using a combination of OCT4 and a small molecule cocktail. This method enables generation of A2B5+ (an early marker for OPCs) iOPCs within 2 weeks retaining the ability to differentiate into MBP-positive mature oligodendrocytes. RNA-seq analysis revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Weider et al ( 76 ) reported that overexpression of SOX10 drives the cellular properties of peripheral satellite glia to resemble those of oligodendrocytes in vivo . Recent attempts to convert human fibroblasts into iOPCs has been also successful ( 77 ). Ectopic expression of OCT4, along with small molecules, directly converts human fibroblasts into expandable iOPCs.…”
Section: Direct Conversion As An Alternative To Differentiationmentioning
confidence: 99%
See 3 more Smart Citations
“…Weider et al ( 76 ) reported that overexpression of SOX10 drives the cellular properties of peripheral satellite glia to resemble those of oligodendrocytes in vivo . Recent attempts to convert human fibroblasts into iOPCs has been also successful ( 77 ). Ectopic expression of OCT4, along with small molecules, directly converts human fibroblasts into expandable iOPCs.…”
Section: Direct Conversion As An Alternative To Differentiationmentioning
confidence: 99%
“…Despite the great efforts aimed to successfully generate human iOPCs, the mechanism of the transcription factors used in the conversion process is still not clearly understood. Yun et al ( 77 ) employed OCT4 as a pioneer factor governing the opening of chromatin regions otherwise generally inaccessible in differentiated cells ( 78 , 79 ). In line with this, Dehghan et al ( 80 ) reported that the forced expression of OCT4 in combination with the administration of valproic acid to the demyelinated mouse brain enhanced myelin sheath repair, providing evidence for functional link between an OCT4 and the regulation of myelin related factors.…”
Section: Direct Conversion As An Alternative To Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…MS iPSCs may be an alternative source of disease relevant cell types that possess the full genetic component of MS risk from an individual with MS. iPSCs are ideally suited to studying the genetics of MS, however, the imprint of lifestyle and environmental factors, in the form of epigenetic modifications are lost during reprogramming (Kim et al, 2010). Epigenetic changes likely contribute to MS development and progression (Küçükali et al, 2015), but only direct reprogramming, which converts a mature cell type directly into another mature cell type, can preserve epigenetic signatures, and offer an alternative in vitro approach for studying the epigenetics of MS (Chanoumidou et al, 2021;Yun et al, 2022).…”
Section: Benefits and Limitations Of Utilising Ipscs For Ms Researchmentioning
confidence: 99%